2017
DOI: 10.1016/j.toxlet.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different anesthetics on tumor cytotoxicity by natural killer cells

Abstract: A number of retrospective studies have suggested that choice of anesthetic drugs during surgical tumor resection might affect tumor recurrence/ metastasis, or outcome of patients. The recent study showed that volatile anesthetics-based general anesthesia was associated with the worse outcomes than intravenous anesthetics-based general anesthesia. However, the underlying mechanism is yet to be determined. Because natural killer (NK) cells are implicated as important immune cells for tumor recurrence/ metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 42 publications
(43 reference statements)
3
44
0
1
Order By: Relevance
“…In addition, Cho et al [ 25 ] demonstrated that the cytotoxicity of NK cells decreased postoperatively in patients who received sevoflurane-remifentanil. In the present study, the suppression of NK cell-mediated cytotoxicity by sevoflurane is consistent with the results of previous studies [ 23 25 ]; however, the research on the effects of sevoflurane on the expression of NK cell ligands remains scarce, which necessitates further evaluation of this field.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, Cho et al [ 25 ] demonstrated that the cytotoxicity of NK cells decreased postoperatively in patients who received sevoflurane-remifentanil. In the present study, the suppression of NK cell-mediated cytotoxicity by sevoflurane is consistent with the results of previous studies [ 23 25 ]; however, the research on the effects of sevoflurane on the expression of NK cell ligands remains scarce, which necessitates further evaluation of this field.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research demonstrated that sevoflurane directly inhibits NK cell activity [ 23 25 ]. Tazawa et al [ 23 ] found that sevoflurane attenuated NK cell-mediated conjugation, polarization, and cytotoxicity by inhibiting leukocyte function-associated antigen-1 in NK cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 A decreased expression of the adhesion molecule leukocyte-associated antigen-1 has been proposed as one of the mechanisms by which isoflurane and sevoflurane suppress the function of NK cells. 31 In contrast, propofol can stimulate the function of NK cells by increasing the expression of granzime B and IFNγ activating surface receptors (CD16, NKp30, NKp44, and NKG2D), and inhibiting prostaglandin E2 formation. 32–34 It is worth considering that the immunomodulatory effects of general anesthetics have been evaluated in vitro in NK cells; therefore, it remains to be determined whether the function of NK cells and lymphocytes is altered in the GBM microenvironment in vivo.…”
Section: Impact Of Anesthetics and Analgesics On Gbm Progressionmentioning
confidence: 99%
“…Isoflurane upregulates hypoxia‐inducible factor‐1 (HIF‐1), the overexpression of which is heavily implicated in tumorigenesis, cancer‐cell invasion, and poor survival outcomes . In cell cultures, isoflurane and sevoflurane have been shown to impair natural killer cell‐mediated cytotoxicity, which is critical to minimize postresection tumor recurrence . In addition, isoflurane has also been shown to promote the malignant potential of lung cancer and glioblastoma stem cells…”
Section: Introductionmentioning
confidence: 99%